2023
DOI: 10.1111/nmo.14689
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene increases the risk of gastroesophageal reflux disease, Barrett's esophagus, and esophageal stricture in postmenopausal women with osteoporosis

Benjamin D. Liu,
Sharon C. Udemba,
Sherif Saleh
et al.

Abstract: Background and AimsEstrogen‐based therapies may increase the risk of gastroesophageal reflux (GERD) and its complications. We aimed to determine the effect of raloxifene on the development of GERD, Barrett's esophagus, and esophageal stricture in postmenopausal women with osteoporosis.MethodsThis was a population‐based, propensity‐matched cohort study using the TriNetX platform. Patients 50 years and older with a diagnosis of “menopause” and “osteoporosis” were included in this study. Odds ratios (OR) and 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Another treatment for osteoporosis is estrogen replacement therapy. Liu's research found that using Raloxifene may increase the risk of several gastroesophageal diseases, such as gastroesophageal reflux disease and Barrett's esophagus in postmenopausal women with osteoporosis [34]. In recent years, finding new drugs for osteoporosis has become a key research area.…”
Section: Discussionmentioning
confidence: 99%
“…Another treatment for osteoporosis is estrogen replacement therapy. Liu's research found that using Raloxifene may increase the risk of several gastroesophageal diseases, such as gastroesophageal reflux disease and Barrett's esophagus in postmenopausal women with osteoporosis [34]. In recent years, finding new drugs for osteoporosis has become a key research area.…”
Section: Discussionmentioning
confidence: 99%